Kepastian Hukum Bagi Konsumen dalam Transaksi Jual Beli Online - Stepanus Ndara; Ida Bagus Anggapurana Pidada (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
Legal protection for consumers in online buying and selling transactions requires confirmation of responsibility related to online buying and selling practices and problems of default caused by business actors. To what extent is the role of the marketplace and business actors responsible for the default losses experienced by consumers? The type of legal research used is empirical juridical legal research. The data sources used are primary data and secondary data. Data collection techniques include interviews, documentation, observation. The data analysis used is qualitative data analysis. The research results obtained by the author are that (1) Buying and selling practices using B2C (Business to Consumer) and C2C (consumer to consumer) transaction systems. (2) Responsibility for legal protection of consumers as a marketplace is related to defaults or unlawful acts caused by business actors, so the burden of responsibility is borne by the business actor by referring to the contract that the parties agreed to. The legal protection provided is limited to supervision, regulators, facilitators, finding solutions, and making decisions regarding defaults or unlawful acts that occur.